FAMILY AS BASIS OF SPIRITUAL GROWTH AND SELF-REALIZATIONS OF PERSONALITY - Коропецька, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the theoretical analysis of concepts “family”, “personality” and «spirituality» is presented, the problem of behavior in family is raised and the main periods of spiritual grout of personality in family are revealed.